The effective use of technology and digitalization in Disaster Management in Malaysia. - Gillani, Syed Muhammad Ahmad Hassan; Raza, Hamad; Qureshi, Muhammad Imran; Khan, Nohman (The journal of contemporary issues in business and government, 2021)
The study will review the literature about disaster management in the Scopus database in 10 years from 2009 to 2018. A review will be done systematically to find out the direction of published and highly cited literature in the policymaking and problem solving after and post-natural disaster in Malaysia. After the complete assessment and filtration of the sheet, only 52 studies are left for the further process. irrelevant literature is screen out and relevant research is analyzed for further process. flood management and landslides are widely discussed challenges and problems in Malaysia. But the flood hazard management in Malaysia is developing rapidly, although the country is a new industrial developed country. The growth and development of social pace, fast-growth political and economic changes and that also charging up the pace of physical and environmental changes. Landslides are also growing with the period in Malaysia and some parts of the country are victims near the residential areas during the monsoon period. It's alarming that the residential areas are in the potential risk of landslides and the highways in some parts of the mountain area of the country.